COVID-19 IMPACT ON NEWSPAPER BUSINESS MODEL CHANGE - Abdullah Sammy; Anton Wachidin Widjaja (President University, 2021)
Covid-19 pandemic causing major shock to the business environment. One of the most affected business environment are newspaper business. Newspaper business that was previously always able to survive in the midst of various disruptions of time, now it is difficult to repeat the ‘glories’ of the past. Because Covid-19 has limited physical interactions which have resulted in disruption of all newspaper business activities starting from the production, distribution, and consumption. This situation left newspaper organizations with little choice but to innovate their business models. This research uses quantitative methods by distributing samples in 30 national newspapers in Indonesia. The purpose of this research is to reveal the strategic steps taken by the Indonesian newspaper business in order to survive from Covid-19 crisis. Keywords: Covid-19 Turbulance, Digital Innovation, Newspaper Business, Business Model innovation